Studying spaces in networked learning - Lei, Yuhong; Oztok, Murat (Proceedings of the International Conference on Networked Learning, 2024)
As universities are making huge efforts on newly emerged learning spaces to accommodate the technologies involved in networked activities (Boys, 2014), it is important to know what students’ practical preference of the study spaces on campus are. This paper found four types of study spaces on campus that international postgraduate researchers preferred, including university libraries, university postgraduate researchers’ offices, student accommodations, and university cafés. However, due to the impact of COVID-19 pandemic, in the United Kingdom, higher educational institutions had to move almost all the learning activities online. This paper concerned international postgraduate researchers’ learning experience during the lockdown in 2020 in the UK. At that time, many international postgraduate researchers often faced difficulties of lacking both learning resources and learning connections in the community and losing access to the study space they preferred previously on campus. This paper found students have different learning experiences during this period. While isolation brought negative impacts on some international postgraduate researchers’ learning experience and connections with others in the community, others have not been influenced by it or even have benefited from it. These contrary learning experiences were mainly associated with students’ different preferences for study spaces, ways of communication, and methods of having connections with others in the community on campus. Finally, the authors suggest that universities should change postgraduate students’ offices and accommodations to enhance students’ learning outcomes.